1300: The Waiting for the New Times Guglielma and Dolcino da Novara (Doctor Virtualis, 2025)
The year 1300 shows a prophetic context and eschatological expectation that prompts the investigations of the inquisitors of heretical pravity who intervene against heretics and heretics who show non-conformist thinking.The turning point of 1300 shows original reflections on the feminine Holy Spirit (in Milan with Guglielma) or a prophetic-apocalyptic preaching (with friar Dolcino from Novara) or apocalyptic positions (with the Catalan doctor Arnaldo from Villanova).Not only the aspiration to a more just society emerges (through the manifestation of the divine Spirit), but also new political-religious developments through the expectation of a new dux or imperator, as well as a papa sanctus or angelicus, mediated through the theological models imposed by the inquisitors.
Keywords: Heresy; inquisition; Guglielma of Milan; Dolcino of Novara